Characterization process to measure the electrical contact resistance of Gas Diffusion Layers under mechanical static compressive loads. (14th September 2017) - El Oualid, S.; Lachat, R.; Candusso, D.; Meyer, Y.
Abstract: Recent research has identified the mechanical properties of the fuel cell internal components (in particular, the Gas Diffusion Layers – GDLs) as key-parameters to obtain high final performances of the generator. The mechanical compression modulus of these components, the stability of their mechanical properties with respect to temperature and humidity, and their ability to interact with water have an impact on the electrical contact resistances in the stack and, by consequence, on the overall performance of the electric generator. Reducing the losses by contact resistance is an objective necessary to optimize the fuel cells in operation. The study of GDL electrical behavior under various internal operating conditions provides a suitable database to better understand their effects on the overall stack performance. This paper describes an experimental method for measuring the electrical contact resistance versus the static mechanical pressure applied to the GDLs. A nonlinear behavior of the electrical contact resistance versus the mechanical stress is observed. The PTFE and MPL additions modify the electrical contact resistance. Highlights: Three industrial GDLs are tested under static electromechanical excitations. A specific ex-situ electrical characterization method is developed. The electrical contact resistance is nonlinear versus the mechanical pressure. The electrical contact resistance decreases versus pressure at room temperature. The PTFE and MPL additions to the GDLs modify the electrical contact resistance.